2009
DOI: 10.1016/j.jana.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Risk Factors Among Male-to-Female Transgender Persons: A Review of the Literature

Abstract: Male-to-female (MTF) transgender women experience a host of psychosocial issues such as discrimination, stigmatization, and marginalization. These challenges often limit economic opportunities, affect mental health, and may place members of this population at an increased risk for HIV infection. This report presents a review of the literature that focuses on risk factors for HIV infection specific to the MTF population. Factors including needle sharing and substance abuse, high-risk sexual behaviors, commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
141
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(157 citation statements)
references
References 25 publications
12
141
2
2
Order By: Relevance
“…Such stigmatizing attitudes by medical practitioners further reduced MSM's willingness to access services, hence promoting the spread of HIV infection among them. Other studies in Indonesia and elsewhere have identified judgemental behaviours to preclude transgender population and motorcycle taxi drivers (tukang ojek) from accessing HIV/AIDS-related information, predisposing them to continuous engagement in HIV risky sexual behaviours (De-Santis, 2009;Fauk & Mwanri, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Such stigmatizing attitudes by medical practitioners further reduced MSM's willingness to access services, hence promoting the spread of HIV infection among them. Other studies in Indonesia and elsewhere have identified judgemental behaviours to preclude transgender population and motorcycle taxi drivers (tukang ojek) from accessing HIV/AIDS-related information, predisposing them to continuous engagement in HIV risky sexual behaviours (De-Santis, 2009;Fauk & Mwanri, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Condomless anal intercourse, sex with multiple partners, illicit drug use, and involvement in commercial sex work (CSW) are demonstrated behavioral risk factors for HIV among transgender women of color (TWOC). 4,[7][8][9] Some suggest that these behaviors are determined by the co-occurrence of poor mental health and substance use linked to social inequality, 8,[10][11][12] also referred to as a syndemic, 13 among TWOC. Thus, there has been a call for interventions focusing on contextual, including social and structural, determinants of the HIV-related syndemic for TWOC.…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on HIV risk among transgender people worldwide has shown that these populations often have high HIV prevalence rates, and increased risk of HIV transmission (De Santis 2009;Nuttbrock, Hwahng, Bockting, Rosenblum, Mason, Macri, et al 2009;Silva-Santisteban, Raymond, Salazar, Villayzan, Leon, McFarland, et al 2011). This research has mainly focused on transgender women, but Stephens, Bernstein and Philip (2010), in a study in San Francisco, USA, found no difference in rates of sexually transmitted infections and HIV between transgender men and transgender women.…”
Section: Introductionmentioning
confidence: 99%